Arthroscopic Reconstruction of Intratendinous Lesions of the Supraspinatus Tendon – a Systematic Review - von Knoch, Marius; Frosch, Stephan; Lehmann, Wolfgang (Zeitschrift für Orthopädie und Unfallchirurgie, 2018)
Background Intratendinous lesions of the rotator cuff of the shoulder are frequent and may be a distinct clinical entity. Nevertheless, there are only a few publications which deal specifically with this subject. This study analyses the existing literature for the arthroscopic reconstruction of the intratendinous lesion of the supraspinatus tendon, by means of a systematic review, and identifies relevant research questions for future studies.Material and Methods In January 2017, a systematic review of the U. S. National Library of Medicine/National Institutes of Health (PubMed) Database and the Cochrane Library was conducted using the PRISMA checklist. The search words were “supraspinatus” and “interstitial”; “supraspinatus”, “tear” and “intratendinous”; “supraspinatus” and “concealed”. In the course of the review, articles written in English with at least a partial arthroscopic case series dealing with the reconstruction of the supraspinatus tendon were identified and further analysed.Results Primarily 70 hits could be generated. Five articles met the inclusion criteria and were analysed in detail. The number of arthroscopic cases ranged between 6 and 33. Level of evidence was IV in all studies. The diagnosis of an intratendinous lesion was made by MR imaging when T2/fat-saturated sequences showed an intratendinous high intensity signal without disruption of the bursal or articular layer. Three different concepts were followed in surgical treatment: opening of the intratendinous lesion from the bursal or articular side or by complete resection of the lesion. The reconstruction was performed with suture anchors in all cases. In the majority of cases, an acromioplasty was also performed. The reported clinical results were mostly good. Healing of the tendon was shown by MR imaging in 81.5 to 100% of cases.Conclusion After failure of conservative treatment, symptomatic intratendinous lesions of the supraspinatus tendon can be localised intraoperatively and reconstructed after failure of conservative treatment. The expected results are good in the medium term. The evidence level of the studies analysed was low. Future studies should examine the role of alternative conservative and surgical therapies.Hintergrund Intratendinöse Läsionen der Rotatorenmanschette der Schulter treten in relevanter Fallzahl auf und stellen möglichweise eine eigene klinische Entität dar. Dennoch gibt es bislang wenig Fachliteratur, die sich spezifisch hiermit beschäftigt. Die hier vorliegende Arbeit analysiert anhand eines systematischen Reviews die vorhandene Fachliteratur zur arthroskopischen Rekonstruktion der intratendinösen Läsion der Supraspinatussehne und ermittelt relevante Forschungsfragen für zukünftige Studien.Material und Methoden Im Januar 2017 wurde eine systematische Durchsicht der Datenbank U. S. National Library of Medicine/National Institutes of Health (PubMed) und der Cochrane Library unter Anwendung der PRISMA-Checkliste durchgeführt. Als Suchwörter dienten „supraspinatus“ und „interstitial“; „supraspinatus“, „tear“ und „intratendinous“; „supraspinatus“ und „concealed“. Anhand der Durchsicht der gefundenen Literatur wurden Artikel mit zumindest anteiligen arthroskopischen Fallserien mit einer Rekonstruktion der Supraspinatussehne in englischer Sprache identifiziert.Ergebnisse Es konnten primär 70 Treffer generiert werden. Fünf Artikel entsprachen den Einschlusskriterien und wurden weitergehend inhaltlich analysiert. Die arthroskopische Fallzahl lag zwischen 6 und 33. Die Evidenz betrug ohne Ausnahme Level IV. Die Diagnose wurde kernspintomografisch gestellt, wenn eine intratendinöse Signalanhebung in der Supraspinatussehne in T2-/fettgesättigten Sequenzen ohne Durchbrechung nach bursal oder artikulär zu erkennen war. Drei verschiedene Konzepte wurden in der operativen Behandlung verfolgt: Eröffnung der intratendinösen Läsion von bursal, von artikulär oder Eröffnung durch komplette Resektion des betroffenen Sehnenanteils. Die Rekonstruktion erfolgte jeweils mit Fadenankern. In der Mehrzahl der Fälle wurde zusätzlich eine Akromioplastik durchgeführt. Die berichteten klinischen Ergebnisse waren mehrheitlich gut. Kernspintomografisch gesicherte Einheilungsquoten lagen zwischen 81,5 und 100%.Schlussfolgerung Symptomatische und therapierefraktäre intratendinöse Läsionen der Supraspinatussehne können intraoperativ lokalisiert und rekonstruiert werden. Die zu erwartenden Ergebnisse sind mittelfristig gut. Der Evidenzlevel der analysierten Studien war für das Fachgebiet niedrig. Zukünftige Studien sollten die Rolle alternativer konservativer und operativer Therapieansätze untersuchen.
Keywords: supraspinatus tendon; intratendinous lesion; repair; arthroscopic; systematic review